Between tradition and contemporaneity.: Analysis of the scenic proposals of folk dance in Bogotá and its relationship with district incentive policies. (The Voz a Vos Bulletin, 2022)
The text presents a contextualization that shows how modern thought has established and highlighted the tension between tradition and contemporaneity, also addressing some ideas of the museification and patrimonialization processes that take place around the staging of traditional dance. Different trends of the artistic projection of traditional Colombian dance are also presented, characterizing them from the practices carried out by directors.
Keywords: Tradition; traditional colombian dance; folklore; contemporaneity; modernity